Factors Influencing Survival in Stage IV Colorectal Cancer: The Influence of DNA Ploidy. (4th June 2013) - Xynos, Ioannis D.; Kavantzas, Nicolaos; Tsaousi, Smaro; Zacharakis, Michalis; Agrogiannis, George; Kosmas, Christos; Lazaris, Andreas; Sarantonis, John; Sougioultzis, Stavros; Tzivras, Dimitrios; Polyzos, Aris; Patsouris, Efstratios S.; et al.
Abstract : Objective . To evaluate the prognostic significance of microscopically assessed DNA ploidy and other clinical and laboratory parameters in stage IV colorectal cancer (CRC). Methods . 541 patients with histologically proven stage IV CRC treated with palliative chemotherapy at our institution were included in this retrospective analysis, and 9 variables (gender, age, performance status, carcinoembryonic antigen, cancer antigen 19-9, C-Reactive Protein (CRP), anaemia, hypoalbuminaemia, and ploidy (DNA Index)) were assessed for their potential relationship to survival. Results . Mean survival time was 12.8 months (95% confidence interval (CI) 12.0–13.5). Multivariate analysis revealed that DNA indexes of 2.2–3.6 and >3.6 were associated with 2.94 and 4.98 times higher probability of death, respectively, compared to DNA index <2.2. CRP levels of >15 mg/dL and 5–15 mg/dL were associated with 2.52 and 1.72 times higher risk of death, respectively. Hazard ratios ranged from 1.29 in patients mild anaemia (Hb 12–13.5 g/dL) to 1.88 in patients with severe anaemia (Hb < 8.5 g/dL). Similarly, the presence of hypoalbuminaemia (albumin < 5 g/dL) was found to confer 1.41 times inferior survival capability. Conclusions . Our findings suggest that patients with stage IV CRC with low ploidy score and CRP levels, absent or mild anaemia, and normal albumin levels might derive greatest benefit from palliative chemotherapy.